2012
DOI: 10.5897/ajb12.1551
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Andrographis paniculata Nees: Analysis of genetic fidelity and andrographolide content in micropropagated plants

Abstract: Andrographis paniculata Nees is a valuable medicinal plant which yields the therapeutic compound andrographolide. The objective of the present study was to develop reliable in vitro propagation techniques in this plant species. The efficiency of shoot regeneration in A. paniculata was tested on the Murashige and Skoog (MS) medium supplemented with 6-benzylaminopurine (BAP), thidiazuron (TDZ), kinetin (Kn) and 2-isopentenyl adenine (2-iP) at concentrations of 0.5, 1.0, 2.0, 5.0 and 10.0 μM and BAP (1.0 μM) in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…1. The results from the current study were in agreement with the findings reported by Vijayalaxmi and Hosakatte [39] which demonstrated that maximum rooting was on half strength MS medium supplemented with 2.0 μM IBA. The enhancing effect of NAA over IBA on rooting in microshoots were reported by a range of worker during in vitro micro-propagation of medicinal plant [40], which also contradictory with our present study.…”
Section: Adventitious Root Induction In Microclonessupporting
confidence: 93%
“…1. The results from the current study were in agreement with the findings reported by Vijayalaxmi and Hosakatte [39] which demonstrated that maximum rooting was on half strength MS medium supplemented with 2.0 μM IBA. The enhancing effect of NAA over IBA on rooting in microshoots were reported by a range of worker during in vitro micro-propagation of medicinal plant [40], which also contradictory with our present study.…”
Section: Adventitious Root Induction In Microclonessupporting
confidence: 93%
“…The performance of IBA and IAA in adventitious root development in A. paniculata was also evident in several in vitro studies. A higher auxin concentration was reported to be more effective for adventitious rooting in shoot cuttings (Dandin & Murthy, 2012; Purkayastha et al., 2008). Higher dosages of IBA were more efficient at inducing adventitious roots in A. paniculata than IAA.…”
Section: Discussionmentioning
confidence: 99%